TRICKLE DOWN ECONOMIC, ATRIBUT PRODUK BANK SYARIAH DAN GOING CONCERN USAHA MIKRO, KECIL DAN MENENGAH - Toto Sukarnoto (Ecobankers : Journal of Economy and Banking, 2020)
Economic growth is the development of activities in the economy which causes the goods and services produced in the society to increase. Economic growth is an increase in gross domestic product or real gross national product. Islamic bank innovative products in the form of sharia restricted account intermediary (SRIA) which will be the differentiator with conventional banks are expected to become game changers, because it will open up investment opportunities in micro, small and medium enterprises by acting as an investment manager because investors are actually SRIA investors themselves. with a variety of product attributes in enhancing the role of Islamic banks in improving the economy of the people so that the existence of Islamic banks with product attributes to be partners who need each other and trickle down the economy will provide opportunities for economic actors in improving welfare. Micro, small and medium enterprises will be able to absorb a large workforce, thereby reducing unemployment. at the same time as the reduction in unemployment will reduce poverty, this is because the workforce absorbed by micro, small and medium enterprises will get income. an increase in income will in turn encourage national consumption so as to stimulate higher production and increase national income so that the development process can continue and the welfare of the community increases Abstrak Pertumbuhan ekonomi merupakan perkembangan kegiatan dalam perekonomian yang menyebabkan barang dan jasa yang diproduksikan dalam masyarakat bertambah. Pertumbuhan ekonomi merupakan kenaikan PDB atau PNB rill. Produk inovatif bank syariah berupa Sharia Restricted Intermediary Account (SRIA) yang akan menjadi pembeda dengan bank konvensional diharapkan dapat menjadi game changer, karena akan membuka peluang investasi di usaha UMKM dengan bertindak selaku manajer investasi, karena pemodal sebenarnya adalah investor SRIA sendiri. Dengan berbagai atribut produk inovatif dalam meningkatkan peran bank syariah terhadap peningkatan ekonomi umat sehingga keberadaan bank syariah dengan atribut produknya menjadi mitra yang saling membutuhkan dan trickle down economic atau ekonomi yang menetes akan memberikan peluang-peluang bagi pelaku ekonomi dalam meningkatkan taraf kesejahteraan. UMKM akan dapat menyerap tenaga kerja yang besar, sehingga akan mengurangi pengangguran. Pada saat bersamaan dengan berkurangnya pengangguran maka kemiskinan akan berkurang, hal ini dikarenakan tenaga kerja yang terserap oleh UMKM akan memperoleh pendapatan. Adanya peningkatan pendapatan pada gilirannya akan mendorong konsumsi nasional sehingga memacu produksi lebih tinggi dan menjadikan pendapatan nasional menjadi meningkat sehingga proses pembangunan dapat terus berjalan dan kesejahteraan masyarakat akan meningkat.